EVALUATION OF MANAGEMENT OF TIBIAL NON-UNION DEFECT WITH ILIZAROV FIXATOR - ullah, Farman; Khan, Muhammad Shoaib; Awais, Syed Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Tibial bone defect lead to limb shortening and functional deficit and needs proper treatment. There are various treatment modalities for bone defect in long bone to restore length and function of the limb, i.e. bone grafting, vascularised bone graft, allograft and bone transport. Bone transport can be done through fixators (uniplaner or ring) and intramedullary nail system. This study was conducted on management of tibial non-union with Illizarov external fixator. METHOD: This descriptive study was performed on 58 patients in Agency Headquarter Hospital, Bajawar and Lady Reading Hospital, Peshawar, from January 2000 to January 2006. Patients of either gender with age between 9 to 58 years, having nonunion (clean and infected nonunion) in tibia with defect of 2 to 7cm due to trauma or firearm injury were included in the study. These patients were followed up upto one year. Outcome measures were according to the classification of Association for the Study and Application of the Method of Ilizarov (ASAMI), which is based on radiological (defect filling) and clinical (functional) findings. RESULTS: Out of 58 patients, 44 (75%) were male and 14 (25%) were female. Mean age was 30 years (9 to 58 years). 38 (65.52%) patients had infected non-union while 20 (34.48%) had clean non-union. Right tibia was involved in 32 patients (51.17%) and left was involved in 26 (44.83%) patients. The cause of initial trauma was road traffic accident in 27 patients (46.55%), firearm injury in 23 patients (39.65%) and a simple fall in 8 patients (13.79%). The length of average bone defect was 2.90 cm (200-7.00cm). Radiological results were excellent in 33 (58.89%) patients, good in 12 (20.68%) patients, fair in 8 (13.79%) patients and poor in 5 (8.62%) patients. The clinical results were excellent in 33 patients (56.89%), good in 18 patients (31.05%), fair in 4 (6.89%) patients and poor in 3 patients (5.17%). CONCLUSION: Ilizarov ring fixator is excellent treatment modality for tibial non-union with a defect, regarding bone union, deformity correction, infection eradication, limb length achievement and limb function but this needs prolonged learning curve for fresh orthopedic surgeons. Key words: Tibia; Nonunion; Bone Transport; Ilizarov fixator